Community Structure and Distribution Pattern of Intertidal Invertebrate Macrofauna at Some Anthropogenically Influenced Coasts of Kathiawar Peninsula (India). (5th August 2014) - Bhadja, Poonam; Poriya, Paresh; Kundu, Rahul
Abstract : Present communication reports the community structure and distribution pattern of intertidal invertebrate macrofauna at four shores of the Kathiawar peninsular coastline off the Arabian Sea (India). The selected shores have different levels of human activities. Present report tests three hypotheses; that is, (i) distribution of invertebrate macrofauna in these shores is influenced by space and time, (ii) abiotic factors have a profound influence on the distribution pattern of intertidal macrofaunal assemblages, and (iii) human activities influence the community structure of the intertidal invertebrate macrofauna at these shores. To test these hypotheses, spatiotemporal variations in different ecological indices were studied. A total of 60 species from six phyla were considered for the study. High species diversity was recorded during winter and monsoon seasons in almost all the shores studied. It was also evident that a few environmental factors had a cumulative influence on the distribution pattern of intertidal macrofauna. Significant spatial variations in the species diversity and evenness were also observed. Though the shores studied have similar coast characteristics and climatic conditions, they face different levels of human activities. Therefore, the observed variations in the intertidal faunal assemblage were possibly caused by anthropogenic stress.